Development of problem-solving skills in a manufacturing context – a learning factory concept - Gergana Vladova; Philip Wotschack; Patricia de Paiva Lareiro; Martin Krzywdzinski (SSRN Rochester, NY, 2022)
The development and deployment of new technologies in industrial production impact employees' workflows and skill requirements. As the complexity of autonomous technology increases, its precise operation becomes more difficult to grasp for employees responsible for the operation, maintenance, and troubleshooting. This general problem of autonomous systems has been described in research as the 'ironies of automation'. While the need for knowledge and understanding of complex and abstract processes increases, the opportunity for direct feedback and learning is diminished. Subsequently, new challenges for training and skill development arise. Recent research has pointed to the importance of holistic process knowledge - as opposed to specific task knowledge - as an essential foundation for individual problem-solving competence. However, further research on the acquisition of problem-solving competences in an Industry 4.0 context is needed. This paper addresses this issue. We first report results from a laboratory experiment that was carried out in a learning factory, evidencing the importance of process knowledge. Based on our findings, we second develop a learning and training concept focusing on the problem-solving abilities of individuals and teams working with 'smart' self-regulating technologies. We expect that the problem-solving abilities of teams are particularly advantageous in smart, complex production settings. We discuss the validation of the concept in the learning factory that will start this year.
Conference: Proceedings of the 12th Conference on Learning Factories (CLF 2022), 11.-13. April 2022, Fusionopolis, Singapore
Keywords: 330; team; problem-solving; assistance systems; experimantal study; ironies of automation